Contingent valuation a comprehensive bibliography and history - Carson, Richard T.; Edward Elgar Publishing (Northampton, Mass. : Edward Elgar, 2011)
This major reference work--the first of its kind--provides a comprehensive and authoritative introduction to the large and growing literature on contingent valuation. It includes entries on over 7,500 contingent valuation papers and studies from over 130 countries covering both the published and grey literatures.
The historical development of contingent valuation -- Bibliography of contingent valuation papers and studies.
Includes bibliographical references.
Keywords: Contingent valuation -- History; Contingent valuation -- Bibliography; Electronic books